2021
DOI: 10.1111/jfpp.15290
|View full text |Cite
|
Sign up to set email alerts
|

Influence of microwave vacuum drying process parameters on phytochemical properties of sohiong (Prunus nepalensis) fruit

Abstract: Subbulakshmi, 2005). Ripened sohiong fruits are drupe of dark purple color with a smooth surface. The unique color of sohiong fruits is due to the accumulation of anthocyanin, which are essential determinants for the color of many roots, leaves, stems, vegetables, fruits, and seeds (Lin-Wang et al., 2010). Sohiong is a spherical shaped fruit, and the ripened fruits are consumed in raw form. The pulp and juice have a purple color and are commonly used to prepare wine, jam, squash, ready-to-serve (RTS) beverages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 54 publications
3
13
0
Order By: Relevance
“…With the vacuum degree increased, the drying time was decreased. This result was similar to the research of Dash et al (2021), who dried the sohiong fruit by microwave vacuum drying. This might be because the vaporization temperature of moisture decreased as the vacuum degree increased(Dong et al, 2021; Luis et al, 2021).…”
Section: Resultssupporting
confidence: 92%
“…With the vacuum degree increased, the drying time was decreased. This result was similar to the research of Dash et al (2021), who dried the sohiong fruit by microwave vacuum drying. This might be because the vaporization temperature of moisture decreased as the vacuum degree increased(Dong et al, 2021; Luis et al, 2021).…”
Section: Resultssupporting
confidence: 92%
“…CAP in our study reduced the drying rate compared to the NP in contrast to other studies. Although, CAP had no significant impact on drying rate of potatoes (Sun et al, 2020), previous studies usually reported that, CAP reduced the surface resistant, increased water diffusion, and thereby drying time was shortened (Öztekin & Sacilik, 2020;Dash et al, 2021). Furthermore, the pectin solubilizes in the acidic condition that assists to remove the water from fruits or vegetables (Brar et al, 2020).…”
Section: Dryingmentioning
confidence: 99%
“…Before starting the drying process, leaves were washed, and healthy ones were selected. It was then stored at 4 ± 0.1 o C and relative humidity of 90 ± 5% until the drying process (Dash et al, 2021;Jahanbakhsi et al, 2020).…”
Section: Fresh Materialsmentioning
confidence: 99%